2022
DOI: 10.1021/acsinfecdis.1c00117
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Phage–Antibiotic Combinations against Citrobacter amalonaticus

Abstract: Non-antibiotic alternative treatments to combat the increasing number of infections caused by multidrug resistant bacteria are urgently needed. In recent years, bacteriophages have reemerged to potentially replace or complement the role of antibiotics, as bacterial viruses have the ability to inactivate pathogens. This study aimed to evaluate the synergy of phage–antibiotic combinations. A Citrobacter amalonaticus isolate was used in this study together with the phage MRM57. Eight different antibiotics with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
2
38
2
1
Order By: Relevance
“…Several in vitro studies have shown a synergistic effect between antimicrobials and antipseudomonal bacteriophages; however, such phenomena are not always observed. This may be explained by the mechanism of action of antimicrobials and the difference in the required environmental factors for biofilm formation; the latter can also be a reason for the disparity in laboratory and clinical results ( 8 , 36 , 37 ). Case reports on the management of P. aeruginosa periprosthetic joint infection and aortic graft infection have demonstrated the synergistic effect of phages and antibiotics, including ceftazidime, which led to the resolution of biofilm-associated infections ( 10 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have shown a synergistic effect between antimicrobials and antipseudomonal bacteriophages; however, such phenomena are not always observed. This may be explained by the mechanism of action of antimicrobials and the difference in the required environmental factors for biofilm formation; the latter can also be a reason for the disparity in laboratory and clinical results ( 8 , 36 , 37 ). Case reports on the management of P. aeruginosa periprosthetic joint infection and aortic graft infection have demonstrated the synergistic effect of phages and antibiotics, including ceftazidime, which led to the resolution of biofilm-associated infections ( 10 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The idea of the use of phage therapy and antibiotics together was previously proposed by several research teams [ 28 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. When considering such a method to combat STEC, Easwaran et al [ 46 , 63 ] tested the efficacy of phage EcSw administered in combination with kanamycin, chloramphenicol, and/or ampicillin against E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…The study performed in vitro with Citrobacter amalonaticus showed synergistic effects for the use of phage MRM57 (10 3 and 10 6 plaque forming units (PFU/ml) with a sublethal dose of antibiotics with a different mechanism of action (carbenecillin, colistin, fosfomycin, gentamicin, meropenem, cefepime-tazobactam, tigecycline) except for cefotaxime at 1/10 × MIC [ 30 ].…”
Section: Phage–antibiotic Synergymentioning
confidence: 99%